PENERAPAN METODE QUALITY FUNCTION DEPLOYMENT (QFD) SEBAGAI UPAYA UNTUK PENINGKATAN KUALITAS PELAYANAN - Indriani, Sri; Sari, Sanny Andjar (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2011)
Quality of service is a very important factor in an entertainment business. This cases on research of MGM City Club is an entertainment business to the concept of One Stop Entertainment. Includes art galleries, Pub, Lounge, and karaoke.This study aims to analyze the quality of customer services and factors-other factors that can enhance pro-gress for the company. Fulfilling customer expectations and customer satisfaction will bring benefits to the company. To meet consumer expectations, it is necessary to perform design services with quality improvement QFD. The use of these methods can help com-panies focus on improvements that should be made to meet these consumer expecta-tions.Based on this analysis it is known that the highest attribute value of interest rate is "Keamanan saat berada di pub" with a value of 4.73, and the lowest is â€Adanya kemuda-han dalam penyampaian komplainâ€ with the value 4.30. The value of the highest satis-faction level was â€œSound yang memadaiâ€ with a value of 3.83 and the lowest is â€œJumlah meja dan kursi yang memadaiâ€ with a value of 2.54. While the priority for attention by the pub was â€œMelakukan briefing setiap hariâ€ with a value of 1.397.